The effect of metacognitive monitoring feedback on performance in a computer-based training simulation. (February 2018) - Kim, Jung Hyup
Abstract: This laboratory experiment was designed to study the effect of metacognitive monitoring feedback on performance in a computer-based training simulation. According to prior research on metacognition, the accurate checking of learning is a critical part of improving the quality of human performance. However, only rarely have researchers studied the learning effects of the accurate checking of retrospective confidence judgments (RCJs) during a computer-based military training simulation. In this study, we provided participants feedback screens after they had completed a warning task and identification task in a radar monitoring simulation. There were two groups in this experiment. One group (group A) viewed the feedback screens with the flight path of all target aircraft and the triangular graphs of both RCJ scores and human performance together. The other group (group B) only watched the feedback screens with the flight path of all target aircraft. There was no significant difference in performance improvement between groups A and B for the warning task (Day 1: group A – 0.347, group B – 0.305; Day 2: group A – 0.488, group B – 0.413). However, the identification task yielded a significant difference in performance improvement between these groups (Day 1: group A – 0.174, group B – 0.1555; Day 2: group A – 0.324, group B – 0.199). The results show that debiasing self-judgment of the identification task produces a positive training effect on learners. The findings of this study will be beneficial for designing an advanced instructional strategy in a simulation-based training environment. Highlights: A positive learning experience by debiasing overconfidence effect. Performance improvement through the metacognitive monitoring feedback. The effects on calibration of retrospective confidence judgments.